2007
DOI: 10.1186/bcr1675
|View full text |Cite
|
Sign up to set email alerts
|

TP53mutation status and gene expression profiles are powerful prognostic markers of breast cancer

Abstract: Introduction Gene expression profiling of breast carcinomas has increased our understanding of the heterogeneous biology of this disease and promises to impact clinical care. The aim of this study was to evaluate the prognostic value of gene expression-based classification along with established prognostic markers and mutation status of the TP53 gene (tumour protein p53) in a group of breast cancer patients with long-term (12 to 16 years) follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(111 citation statements)
references
References 35 publications
9
95
2
Order By: Relevance
“…This result was supported by the previous studies that p27 of p21 family is an inhibitor of cyclin D1-CDK 4 and cyclin A-CDK 2 complexes, the increased expression inhibits the activity of cyclin D- CDK 4 [48]. p53 mutation is one of the most powerful prognostic markers in breast cancer and is a desirable target gene for therapeutic potential [49-51]. The upregulation of p53 suggested that galangin could inhibit the mutation of MCF-7 cells.…”
Section: Discussionsupporting
confidence: 70%
“…This result was supported by the previous studies that p27 of p21 family is an inhibitor of cyclin D1-CDK 4 and cyclin A-CDK 2 complexes, the increased expression inhibits the activity of cyclin D- CDK 4 [48]. p53 mutation is one of the most powerful prognostic markers in breast cancer and is a desirable target gene for therapeutic potential [49-51]. The upregulation of p53 suggested that galangin could inhibit the mutation of MCF-7 cells.…”
Section: Discussionsupporting
confidence: 70%
“…Another favorable characteristic of the hypermethylated tumors was the observation that none of them had a p53 mutation. Mutated p53 was found to significantly correlate with a greater carcinogenic aggressiveness and worse OS of breast cancer patients (17,(36)(37)(38). Since p53 and BRCA1 are involved in a same cancer pathway, it could be speculated that the inactivation of the pathway does not require inactivation of both genes (inactivation of one gene may be sufficient).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in an analysis of LFS patients, germline missense mutations in TP53 have been shown to be associated with an earlier age of onset (;9 years) when compared with germline deletions in TP53, suggesting a gain-of-function effect of missense p53 mutants in human tumors (Bougeard et al 2008). In addition, multiple studies have also demonstrated that the mutational status of p53 is a strong predictor for poor outcomes in many types of human tumors, particularly breast cancer (Elledge et al 1993;Olivier et al 2006;Langerod et al 2007;Petitjean et al 2007a).…”
Section: Gain-of-function Hypothesismentioning
confidence: 99%